2019
DOI: 10.3926/jotse.504
|View full text |Cite
|
Sign up to set email alerts
|

Learning styles, study habits and academic performance of Filipino University students in applied science courses: Implications for instruction

Abstract: In order to better prepare university students as proficient, versatile and productive information and industrial technologists in the 21st century, the need to implement instructional strategies and activities naturally align with their predispositions will make them better learners. This study examined the learning style preferences, study habits and level of academic achievement of students enrolled in applied science courses of Cagayan State University at Lasam, Philippines.  The study employed descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 19 publications
3
68
1
6
Order By: Relevance
“…With reference to the rubrics for the assessment of the study habits/skills (Table 2), we can also see that the study skills scores of the Taiwanese junior and senior students stand in the mid-range grading continuum; while those of the Taiwanese freshmen and sophomores slope a little lower in the range. This finding somewhat approves Jafari, Aghaei, and Khatony (2019)'s, as well as Magulod (2018)'s claims in that most university students have moderate levels of study habits. Finally, it is interesting to notice that considering all Taiwanese students in this research regardless of which year they are, and based on what they have claimed on the questionnaire, we can see that their strongest study habit is "punctuality in arriving at classes" (item 1; Mean=6.14), while their weakest study habit is "having a system for making textbooks" (item 14; Mean=2.35).…”
Section: Discussionsupporting
confidence: 86%
“…With reference to the rubrics for the assessment of the study habits/skills (Table 2), we can also see that the study skills scores of the Taiwanese junior and senior students stand in the mid-range grading continuum; while those of the Taiwanese freshmen and sophomores slope a little lower in the range. This finding somewhat approves Jafari, Aghaei, and Khatony (2019)'s, as well as Magulod (2018)'s claims in that most university students have moderate levels of study habits. Finally, it is interesting to notice that considering all Taiwanese students in this research regardless of which year they are, and based on what they have claimed on the questionnaire, we can see that their strongest study habit is "punctuality in arriving at classes" (item 1; Mean=6.14), while their weakest study habit is "having a system for making textbooks" (item 14; Mean=2.35).…”
Section: Discussionsupporting
confidence: 86%
“…However, educators should recognize the students learning preference in order to meet the students' strengths in learning (Awla, 2014). Hence, majority of the students try to adapt to different ways of absorbing and processing piece information (Magulod, 2018). Students have different learning perspective unfortunately not all are effective (Fang, Daud, Al Haddad, & Mohd-Yusof, 2017).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The study of Magulod (2018) revealed that most of the learners remember and absorb the information better when they read. Similarly, Fang, Daud, Al Haddad and Mohd-Yusof (2017) study showed that most of the students depend on the pictures being presented particularly…”
Section: Table1 Students Preferred Learning Stylesmentioning
confidence: 99%
“…In a research by Dalmolin et al (2018) it was discovered that there was a positive connection between learning styles and academic performance of students. Magulod Jr. (2019) also conducted a research on learning styles and academic performance and found a significant relationship between learning styles and academic performance of students. The characteristics, strengths and preferences in the form, in which an individual receive and process information, is termed learning styles (Hsieh et al, 2011).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%